PENGETAHUAN LOKAL MASYARAKAT PESISIR PANTAI DAN MITIGASI BENCANA DI SUMATERA BARAT - Rahmadani, Deby; Arifin, Zainal; Rahman, Fajri (FISIP Universitas Malikussaleh, 2024)
This study illustrates how local knowledge of coastal communities on natural disasters including gampo (earthquake), aia gadang (tsunami), aia taganang (flood). There is community preparedness for natural disasters. This research uses qualitative methods with a case study approach, observation data collection techniques, interviews, literature studies and documentation. Selection of informants using purposive sampling. Based on the results of research, people have local knowledge about gampo (earthquake), aia gadang (tsunami), and aia taganang (flood) disasters. This knowledge includes signs of disaster, how new knowledge is then interpreted and interpreted again, giving rise to the geological knowledge they have. People also have reasons to stay afloat in areas prone to natural disasters. Knowledge produces how preparedness includes organizing, appropriate use of resources, and how to hope in God. The Nagari Tapakis community uses their local traditions as a form of belief, namely a) Tolak Bala, b) Grave Pilgrimage, c) Mangaji bulan muluik, d) Mandoa bulan pitah. In addition, the community also has physical development efforts such as a) artificial Muaro, and b) Making evacuation routes.